IPTEK PEMBUATAN MESIN PENGGILING PADI SEBAGAI UPAYA MENINGKATKAN PRODUKTIVITAS PADI DESA PANSUR NAPITU KECAMATAN SIATAS BARITA KABUPATEN TAPANULI UTARA - Utomo, Budi; Tadjung, Kasmir (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Pansur Napitu Village is located in Siatas Barita District, North Tapanuli Regency, North Sumatra Province. This village is 280 km from the city of Medan which can be reached using a four-wheeled vehicle in 7 hours. The village population in general is the Batak tribe which covers 90% of the total population. In general, residents have agricultural main businesses such as rice, corn and other secondary crops. Until now, rice farming is still the mainstay of farmers in this village. Almost 90% of farmers hope for their rice crops. However, farmers experience problems in handling production, where farmers have to pay additional costs to the rice mill warehouse to make it ready for market. These costs are felt to be burdensome for farmers, which results in the income that farmers will receive being relatively low. The entry of the Universitas Sumatera Utara community services team raised new hopes for the community. This activity is also assisted by 3 students who will be trained to take action to resolve this problem. Now with the implementation of a rice milling machine with a capacity of 750 kg/hour which was donated to Pansur Napitu Village, the community has become more independent in carrying out its rice milling and the costs incurred for rice milling can be reduced to become cheaper. Automatically, the community will be more helped by the donated tools.